Evidence from the Dayao Paleolithic site, Inner Mongolia for human migration into arid northwest China during mid-Pleistocene interglacials. (September 2021) - Ge, Junyi; Wang, Yinghua; Shan, Mingchao; Feng, Xingwu; Chen, Fuyou; Wu, Haibin; Li, Qin; Zhou, Xinying; Li, Yan; Tang, Ruiping; Olsen, John W.; Deng, Chenglong; et al.
Abstract: The Dayao Paleolithic site, located in Inner Mongolia on the eastern margin of China's vast northwestern drylands, was a lithic quarry-workshop utilized by Pleistocene human migrants through the region. Determining the age of this activity has previously yielded controversial results. Our magnetostratigraphic and OSL dating results suggest the two artifact-bearing paleosols are correlated with MIS 5 and 7, respectively. Correlating paleoclimatic data with marine δ 18 O records leads us to conclude that two sandy gravel layers containing many artifacts in the lower part of the Dayao sequence were formed during MIS 9 and 11, if not earlier. Our results reveal that the earliest human occupation at the Dayao site occurred before ca. 400 ka during a relatively warm and moist interglacial period, similar to several subsequent occupations, documenting the earliest and northernmost archaeological assemblage yet reported in China's arid northwest. We conclude that the northward and southward displacements of the East Asian summer monsoon rain belt during past interglacial-glacial cycles were responsible for the discontinuous human occupation detected at the Dayao site. The penetration of this precipitation regime into dryland ecologies via the Huanghe (Yellow River) Valley effectively created a corridor for hominin migration into China's arid northwest.